Facts about Calcium - Linda B. Bobroff (EDIS, 2012)
Calcium is the major mineral found in our bones and teeth. Along with phosphorus and other nutrients, calcium builds the hard structure that makes bones and teeth strong. We also need calcium for proper muscle and nerve function, blood clotting, and other body processes. These functions are so critical that calcium is taken from the bones to maintain blood calcium if dietary calcium is inadequate. This revised 3-page fact sheet was written by L. B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, March 2012.